Scarceness of phytoseiid species co-occurrence (Acari: Phytoseiidae) on leafletsof Juglans regia - Jan Kabíček (Plant Protection Science, 2010)
In order to obtain information on the phytoseiid mite taxocoenoses, population density and frequency of occurrence on leaflets of Juglans regia, abandoned and uncultivated trees were sampled from July to August 2007. Eight phytoseiid mite species (Euseius finlandicus, Neoseiulella aceri, Neoseiulella tiliarum, Typhlodromus pyri, Typhlodromus cotoneastri, Phytoseius turiacus, Amblyseius andersoni, Paraseiulus triporus) were identified. Total phytoseiid population density averaged 1.4 mites per leaflet. The most abundant was Euseius finlandicus, and Neoseiulella aceri was the second most common species. The predominant presence of only one phytoseiid species per walnut leaflet was noted, but the co-occurrence of two species (mostly E. finlandicus with N. aceri) was also observed. The simultaneous occurrence of three phytoseiid species on a single leaflet was seldom detected and the cohabitation of more than three species per leaflet was not observed.